Highly Efficient Deep Blue Luminescence of 2-Coordinate Coinage Metal Complexes Bearing Bulky NHC Benzimidazolyl Carbene - Hamze, Rasha; Idris, Muazzam; Muthiah Ravinson, Daniel Sylvinson; Jung, Moon Chul; Haiges, Ralf; Djurovich, Peter I.; Thompson, Mark E. (Frontiers in Chemistry, 2020)
The structural, photophysical and electrochemical properties of three luminescent 2-coordinate coinage metal (i.e. M = Cu, Ag, Au) complexes bearing a sterically bulky benzimidazolyl carbene, 1,3 bis(2,6 diisopropylphenyl)-1-H-benzo[d]imidazol-2-ylidene (BZI), and carbazolide (Cz) as the anionic ligand were investigated. All the complexes emit in the deep blue region ( 430 nm) with relatively narrow (full width at half maximum = 44 nm, 2300 cm-1) and vibronic fine structure in nonpolar media (methylcyclohexane at room temperature), and with high photoluminescence quantum yields (PLQY > 80%) and radiative rate constants (kr 7.8×105 s-1). The luminescence is solvatochromic, undergoing red-shifts in a polar solvent (CH2Cl2) at room temperature that are accompanied by a decrease in quantum yields (PL < 23%) and radiative rate constants (kr < 4.0×104 s-1), whereas the non-radiative rate constants remain nearly constant (knr 1.0×105 s-1). The radiative rate is controlled via thermally assisted delayed fluorescence (TADF) and temperature-dependent luminescence studies of the gold complex (AuBZI) in methylcyclohexane solution reveal an energy difference between the lowest singlet and triplet excited states of 920 cm 1. Organic light-emitting diodes (OLEDs) fabricated using AuBZI as a luminescent dopant have an external quantum efficiency of 12% and narrow, deep-blue emission (CIE = 0.16, 0.06).